Connections teachers make between creativity and arts learning. Issue 4 (2nd October 2018) - Selkrig, Mark
ABSTRACT: Background : Creativity is often cited as one of the capacities that needs to be actively encouraged in all aspects of schooling. However, what creativity is and how it may be promoted through formal teaching and learning approaches remain contested. There are also differences between educators in terms of how they understand, discuss and conceptualise this complex concept. Purpose : This paper focuses on the difficulties associated with talking about creativity in education. It considers the ways in which schoolteachers who are involved in the area of arts education understand, describe and discuss the concept of creativity and how it interacts with their classroom practice. Sample : Twenty-three educators who taught Arts (either as generalist primary classroom teachers or as specialist teachers), and the leadership team from a Kindergarten to Year 9 (pupil ages 5–15) school in the suburbs of a city in the Australian state of Victoria participated in the project. Design and methods : In this phenomenological study, data were gathered from participants through questionnaires, discussion groups, email prompts and reflective journals. The material was analysed qualitatively. Findings : By examining the teachers' dialogic and discursive responses about creativity, it was possible to capture some broad ways in which the participants spoke about creativity. Data were analysed thematically and grouped into categories that represented the connected 'creative orientations': thinking orientations, action orientations, emotion orientations and skill/outcome orientations. Conclusion : There is a need for educators in and across a range of discipline areas to share, map and think about creativity. The approach adopted in this exploratory study offers a way that could be used to focus discussions and help facilitate educators' talk about creativity.